Distributed Edge-Enhanced Imaging With a Fractional Spiral Phase Filter Using Random Light - Wang, Huahua; Ma, Jian; Yang, Zhixin; Du, Haoran; Kang, Xingwang; Su , Hengzhi; Gao, Lu; Zhang, Ze (Frontiers in Physics, 2022)
A gradual edge enhanced ghost imaging method with pseudo-thermal light is proposed in both theory and experiment. In the experiment, a phase object and fractional spiral phase filter (SPF) are placed symmetrically in the imaging plane of the pseudo-thermal light source in the distributed test and reference beams of the lensless ghost imaging system. The procedure of gradual edge enhanced ghost imaging is carried out by modulating the fractional topological charge from 0 to 1. We observe that the brightness of the object edge increases with the increasement of the fractional topological charge. It is also found that the intensity distribution is uniform and isotropic when the topological charge is integer, otherwise, the intensity distribution is not uniform. Theoretical analysis is also provided. The proposed gradual edge enhanced ghost imaging scenario releases the position limitation in the Fourier plane for the filter of the traditional phase filtering imaging process. The method is believed to have prospective applications in microscopic imaging and biomedical detection.